2002
DOI: 10.1080/01926230290166760
|View full text |Cite
|
Sign up to set email alerts
|

Renal Papillary Necrosis

Abstract: Renal papillary necrosis (RPN) is a signi cant problem in human beings, especially in England and in Australia where it has been reported to account for 15% to 20% of patients needing renal transplants. Many compounds , including aspirin, phenacetin, phenylbutazone , indomethacin, mefenamic acid, ufenamic acid, fenopro n, naproxen, and ibuprofen have been linked to renal papillary necrosis in human beings. Although the exact mechanism of RPN is unknown, there are several theories that have good scienti c evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 24 publications
0
25
0
2
Order By: Relevance
“…It has been suggested that the renal papilla of rats and dogs are more susceptible to xenobiotic insult due to sluggish regional blood flow that may predispose to COX-mediated ischemia. The interstitial cells of the renal papilla in the dog and rat have similar expression levels of COX-1 and COX-2, and may be the earliest targets of NSAID inhibition (Brix, 2002). While monkeys developed some renal lesions after treatment, these were attributable to the precipitation of the drug into the renal tubules, and have been previously described (Leach et al, 1999) and were not likely pharmacologically mediated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been suggested that the renal papilla of rats and dogs are more susceptible to xenobiotic insult due to sluggish regional blood flow that may predispose to COX-mediated ischemia. The interstitial cells of the renal papilla in the dog and rat have similar expression levels of COX-1 and COX-2, and may be the earliest targets of NSAID inhibition (Brix, 2002). While monkeys developed some renal lesions after treatment, these were attributable to the precipitation of the drug into the renal tubules, and have been previously described (Leach et al, 1999) and were not likely pharmacologically mediated.…”
Section: Discussionmentioning
confidence: 95%
“…RPN caused by NSAIDs in humans is rare, and is often associated with concomitant factors such as heart disease, hypertension, and dehydration (Brix, 2002). In contrast to humans, the renal medullary arterial blood flow is entirely postglomerular in laboratory animals, therefore changes in glomerular perfusion have effects not only at the cortical level, but also at the medullary level (Brix, 2002;Khan and Alden, 2002). The mechanisms of renal papillary necrosis are uncertain, but are believed to be at least in part due to decreased renal blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, these patients may develop hypertension, cardiac disease, and chronic renal failure. 3,7 In this case, the patient presented with some of these symptoms: general malaise, gastrointestinal complaints, irritative voiding symptoms, and renal colic; however, her imaging was highly unusual as it appeared as an obstructing bladder mass most consistent with an invasive malignancy. As her RPN progressed, the sloughed debris obstructed her left ureter that resulted in renal colic.…”
Section: Discussion and Literature Reviewmentioning
confidence: 90%
“…1 Still, it is likely that several different pathways are at play depending on the underlying cause, and that RPN represents a final common pathway of multiple courses. 1,7–9 Our patient had known diabetes that likely represented her biggest risk factor for RPN. Furthermore, her history of recurrent UTI raises the question of subclinical pyelonephritis preceding her presentation and further increasing her risk for papillary necrosis.…”
Section: Discussion and Literature Reviewmentioning
confidence: 95%
“…In preclinical studies, almost all of the nonsteroidal anti-inflammatory drugs produced papillary necrosis in experimental animal models (Whelton and Hamilton, 1991). A possible mechanism of papillary necrosis is ischemic injury through the direct inhibition of cyclooxygenase-mediated production of prostaglandins (Brix, 2002). However, the inhibition of cyclooxygenase mediated by ZP might not contribute to ZP-induced kidney injury because papillary necrosis was not observed in this injury.…”
Section: Downloaded Frommentioning
confidence: 98%